Big data analysis to understanding online songbird trade in Indonesia: What are the most traded species? - Center for International Forestry Research (Center for International Forestry Research, 2022)
Under the GCRF Trade, Development and the Environment Hub Project (TRADE Hub), the CIFOR research team is studying the wildlife trade in Indonesia with a focus on songbirds. The study is exploring the use of big data analysis and machine learning to monitor songbird trade in the online marketplace.